Protocol-driven multidetector SPECT/CT: integration of hybrid imaging into the routine workflow of whole-body bone scintigraphy in oncology patients. Issue 1 (January 2020) - Adusumilli, P.; Nejadhamzeeigilani, H.; Pitts, K.; McDermott, G.; Scarsbrook, A.F.; Vaidyanathan, S.; Patel, C.N.; Chowdhury, F.U.
Abstract : AIM: To analyse the additional clinical value of protocol-driven and selective use of multidetector single-photon-emission tomography/computed tomography (SPECT/CT) in oncology patients undergoing whole-body bone scintigraphy (BS) and to analyse reporter confidence in diagnosis with and without SPECT/CT. MATERIALS AND METHODS: During a 2-year period, 2, 954 whole-body BS examinations were performed in oncology patients, with 444 (15%) undergoing additional protocol-driven SPECT/CT. Retrospective evaluation of planar BS and SPECT/CT images was performed by two experienced dual-trained nuclear medicine radiologists. The BS and SPECT/CT images were graded blindly using a five-point scale designed to evaluate the likelihood of a lesion being benign or malignant. Interpretation was applied on a per-patient basis. RESULTS: There was a 74.5% increase in definitive diagnostic classification and a 26.6% reduction in equivocal findings with SPECT/CT when compared to BS alone ( p <0001). Of cases initially classified as "probably benign" on BS, 5.1% (10/193) were reclassified to "probably malignant" (1%) or "malignant" (4.1%) using the SPECT/CT data. The highest impact in reporter confidence was seen with SPECT/CT in the interpretation of lesions within the pelvis (34%), ribs (23%), lumbar spine (22%), and thoracic spine (21%). CONCLUSION: Protocol-driven, selective use of SPECT/CT imaging to augment planar BS reduces equivocal findings and improves reporter confidence whilst minimising the impact on patient and reporting workflows. Highlights: SPECT/CT in bone scintigraphy can be used selectively in a protocol-driven manner for oncology patients. SPECT/CT reduces equivocal findings compared to planar BS imaging. SPECT/CT significantly increases reporter confidence in the axial skeleton. Prospective studies are required to evaluate the impact of SPECT/CT on clinical management.